2012
DOI: 10.1016/j.anorl.2011.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration cytology in the management of parotid masses: Evaluation of 249 patients

Abstract: International audienceIntroduction The role of fine-needle aspiration cytology (FNAC) in the management of parotid tumours is still the subject of controversy. The purpose of this study was to determine the diagnostic value of FNAC in our institution in order to define its place in the diagnostic strategy.Patients and methods :This retrospective study was based on 249 patients who had undergone preoperative FNAC before being operated in our institution between 2001 and 2008. All examinations were performed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
10

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 24 publications
2
55
0
10
Order By: Relevance
“…The sensitivity of FNAB clearly seems to be lower than its specificity, which means that the false-negative rate is higher than the false-positive rate (15,16). The relatively high rate of false negatives may limit the usefulness of FNAB.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The sensitivity of FNAB clearly seems to be lower than its specificity, which means that the false-negative rate is higher than the false-positive rate (15,16). The relatively high rate of false negatives may limit the usefulness of FNAB.…”
Section: Discussionmentioning
confidence: 90%
“…A non-diagnostic cytology is one of the major drawbacks of FNAB, and it ranges between 3% and 34% (8,16). This may be due to low cellularity, necrosis, bleeding, or improper technique (3,8).…”
Section: Discussionmentioning
confidence: 99%
“…Fakhry ve arkadaşlarının 249 hastanın parotis kitlelerinde uyguladıkları İİAB sonuçlarına göre lezyonların %75'i benign, %25'i malign bulunmuşlar 16 . Basavanandswami ve arkadaşları parotisteki lezyonların %70'den fazlasının benign tümör olduğunu ifade etmişlerdir 14 .…”
Section: Tartıșmaunclassified
“…Accurate histological classification of the tumour was reported in 79.5% of cases (86% for benign tumours and 44% for malignant tumours). The autors concluded that FNAC is a reliable examination providing important information to the surgeon in the preoperative diagnostic assessment (9).…”
Section: Fine Needle Aspiration Biopsy (Fnab) Fine Needle Aspirationmentioning
confidence: 99%
“…The reported diagnostic accuracy of FNAC can be as high as 98% when adequate material is obtained, but the rate of insufficient or non-diagnostic rate is up to 29% (7,8,9). In another study Р. Zbären , et al was performed preoperative FNAC in 228 and the results of FNAC were analyzed and compared with the corresponding histopathological diagnosis.…”
Section: Fine Needle Aspiration Biopsy (Fnab) Fine Needle Aspirationmentioning
confidence: 99%